Tuvan People’s Republic’s and USSR’s Domestic Loans in Tuva, 1920s – 1940s - Kharunova, Marianna M.-B.; Kharunov, Ramil Sh.; Bazyr, Ruslana N. (The New Research of Tuva, 2020)
In the 1930s–40s, the Government of the People’s Republic of Tuva (PRT) followed the Soviet practices of using personal savings and enterprises’ resources to raise funds to accelerate the republic’s economic advance and reinforce its agricultural sector. To take control of these resources, public bonds were issued. This article, making use of materials preserved at the National Archives of the Republic of Tuva, the 1930s–40-s regional newspapers and collections of the Aldan-Maadyr National Museum of Tuva, for the first time ever attempts to present an overall picture of the issuance, placement and circulation of the USSR and TPR public bonds in the territory of Tuva, as well as of how the borrowed funds contributed to the republic’s economy.The first USSR public bonds (1927, 1928, 1929, 1930 issues) were placed among Soviet professionals on an assignment in Tuva, and among residents of the Russian Self-Administering Workers’ Colony (RSWC). Later on, the Government of Tuva widely used public bonds issued by the USSR. After TPR’s accession to the USSR, the Tuvan government bonds issued in 1942 and 1943 were converted into those issued through the 3rd Public War Loan of the USSR.The article analyzes various methods of the bond placement. For instance, there were planned actions with mandatory bond purchase targets, “Socialist competitions” and obligatory subscription to loans through labor collectives. The bonds were also sold to rural population for cash. The authors also examine the involvement and role of the TPR government and party organs, financial sector, the Tuvan Bank of Industry and Trade and the Committee of Russian Citizens in the campaign of bond placement among the population of Tuva.
Keywords: Tuvan People’s Republic; USSR; public loan; bond; budget; loan subscription; bond conversion